Isu Pembangunan Wakaf Menggunakan Struktur Amanah Pelaburan Hartanah Islam di Malaysia: Satu Tinjauan - Sulaiman, Syahnaz (Kanun: Jurnal Undang-undang Malaysia, 2012)
This paper will discuss one of the mechanisms for developing waqf assets based on contemporary financial instrument structure, namely the Islamic Real Estate Investment Trust (I-REIT). Previous studies have shown that the I-REIT has the pontential of being developed into a mechanism for waqf asset in Malaysia. However, its implementation has been without issues and problems. Hence this prelimenary study offers an insight into the issues related to the development of waqf properties based on the I-REIT within the context of Malaysia. Library research is the main method of collecting data and document perusal and interviews were carried out to inquire into the relevant theories that determine the status and position of the I-REIT as an Islamic compliant vehicle. It is hoped that the findings of this study will firstly, pave the way for the procurement of the much needed Islamic compliant waqf funds and secondly, develop a system of best practices and good and effective governance to increase the confidence of Muslim to waqf. Keywords: waqf, waqf assets, development, Islamic Real Estate Investment trust (I-REIT)